Effective Communication Strategies In Business: The Use Of Ambiguous Sentences To Avoid Communication - RA Nabila Allya Salsabilla; Choiriyah, Choiriyah; Havis Aravik; Fadilla, Fadilla; Dwi Noviani; Emilia Sari (Jurnal Ekonomi Bisnis, Manajemen dan Akuntansi, 2025)
Business communication is a fundamental aspect in ensuring operational efficiency and achieving organizational goals. However, the frequent use of ambiguous sentences in professional communication practices often leads to miscommunication, misinterpretation, and workplace conflict. This study aims to analyze the importance of using unambiguous sentences as a strategy for effective communication in business environments. The research employs a descriptive qualitative approach through literature review and case study analysis of communication within the workplace. The results show that unclear or ambiguous language negatively impacts message comprehension, team coordination, and decision- making processes. On the other hand, delivering messages using structured sentences, standard language, and precise diction significantly enhances work efficiency, strengthens professional relationships, and fosters a healthy communication culture within organizations. This study emphasizes that clarity in language is not merely a linguistic concern but an integral part of strategic management in business. Therefore, communication training, language guidelines, and collective awareness are essential in building professional and productive workplace communication.